PERANCANGAN LANSKAP PANTAI SENDIKI SEBAGAI KAWASAN EKOWISATA DI DESA TAMBAK REJO, KECAMATAN SUMBERMANJING WETAN, KABUPATEN MALANG, JAWA TIMUR - Pain Pati, Petrus Paulus; Setyabudi, Irawan; Nuraini, Nuraini (Universitas Tribhuwana Tunggadewi, 2018)
Sendiki Beach is one of the attractions located precisely in Tambak Rejo Village, Sumbermanjing Wetan Subdistrict, Malang Regency, East Java, which is full of various problems, such as low public awareness in maintaining and caring for environmental quality which affects up to physical and non-physical the area and the ecosystem of the region besides that is also the lack of promotion of tourist areas, so there needs to be a solution to the problem. The purpose of the research is to design the Sendiki Beach landscape based on edu-ecotourism by paying attention to aspects of ecotourism. This research was conducted through site surveys to obtain physical and non-physical data sites, while comparative studies in related libraries were used as references to the design. The research method is carried out qualitatively with data analysis using Focus Group Discussion. The flow of thought used, with the flow of thought from Gold and Rustam Hakim, adjusted to the science of agriculture and education. The design stage starts from the initial preparation, identifies physical, biophysical, socio-cultural and economic aspects, ecology, analysis and synthesis, determines design (ethnic and natural) themes and programatic design concepts. The design of the Sendiki Beach landscape uses the concept of social culture and nature with a blend of local culture and is supported by aspects of ecotourism, by means of integrating the social cultural values of the community and maintaining environmental conditions that are in harmony between human life and the surrounding environment. The results obtained are in the form of the design of the tourist landscape of Sendiki Beach as an ecotourism area (edu ecotourism). The conclusion of landscape design is in the form of a coastal landscape design or design that accommodates and supports the sharing of site user activities by paying attention to design concepts and paying attention to the objectives of the landscape design, namely the edu ecotouriesm area. Pantai Sendiki merupakan salah satu obyek wisata yang terletak tepatnya di Desa Tambak Rejo, Kecamatan Sumbermanjing Wetan, Kabupaten Malang, Jawa Timur, yang sarat dengan berbagai masalah, misalnya rendahnya kesadaran masyarakat dalam menjaga dan merawat kualitas lingkungan yang berdampak sampai pada masalah fisik dan non fisik kawasan serta ekosistem kawasan disamping itu juga kurangnya promosi terhadap kawasan wisata, sehingga perlu adanya solusi atas masalah tersebut. Tujuan penelitian yakni Merancang lanskap Pantai Sendiki berbasis edu-ecotourism dengan memperhatikan aspek-aspek ekowisata. Penelitian ini dilakukan melalui survei lokasi untuk mendapatkan data fisik maupun non fisik tapak, sedangkan studi komperatif berupa pustak-pustaka terkait digunakan sebagai refrensi terhadap perancangan. Metode penelitian dilakukan secara kualitatif dengan Analisis data menggunakan Focus Group Discussion. Adapun alur pikir yang digunakan, dengan alur pemikiran dari Gold dan Rustam Hakim, disesuaikan terhadap ilmu pertanian dan pendidikan. Tahapan perancangan dimulai dari persiapan awal, mengidentifikasi aspek fisik, biofisik, sosial budaya dan ekonomi, ekologi, analisis dan sintesis, menentukan tema perancangan (etnik dan natural) serta konsep desain programatik. Perancangan lanskap Pantai Sendiki menggunakan Konsep social cultuur and nature dengan perpaduan budaya masyarakat setempat dan didukung oleh aspek ekowisata, dengan dimaksud dapat memadukan nilai sosial budaya masyarakat serta terpeliharanya kondisi lingkungan hidup yang selaras antara kehidupan manusia dengan alam sekitarnya. Hasil yang diperoleh berupa rancangan lanskap wisata Pantai Sendiki sebagai kawasan ekowisata (edu ecotourism). Kesimpulan dari desain lanskap yakni berupa rancangan atau desain lanskap pantai yang menampung dan mendukung berbagi aktifitas pengguna tapak dengan memperhatikan konsep-konsep desain serta memperhatikan tujuan dari dari desain lanskap yakni sebagai kawasan edu ecotouriesm.